2022
DOI: 10.3390/epigenomes6020015
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Genetics, Epigenetics, and the Environment in ASD: A Mini Review

Abstract: According to recent findings, variances in autism spectrum disorder (ASD) risk factors might be determined by several factors, including molecular genetic variants. Accumulated evidence has also revealed the important role of biological and chemical pathways in ASD aetiology. In this paper, we assess several reviews with regard to their quality of evidence and provide a brief outline of the presumed mechanisms of the genetic, epigenetic, and environmental risk factors of ASD. We also review some of the critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…This anticonvulsant drug is widely employed as an inducer of ASD in animal models across various species [7][8][9][10]. Consistent with findings in autistic humans, exposure to VPA during embryogenesis in zebrafish, is associated with behavioral, neuroanatomical, and genetic alterations, along with deficits in neuronal connectivity and neurotransmitter expression [11][12][13][14][15]. The zebrafish model of ASD offers methodological advantages, including high socialization within the species, prolific reproductive performance, a broad behavioral repertoire, physiological and genetic homology, and neuroanatomical similarity to mammalian species, including humans [13].…”
Section: Introductionmentioning
confidence: 71%
“…This anticonvulsant drug is widely employed as an inducer of ASD in animal models across various species [7][8][9][10]. Consistent with findings in autistic humans, exposure to VPA during embryogenesis in zebrafish, is associated with behavioral, neuroanatomical, and genetic alterations, along with deficits in neuronal connectivity and neurotransmitter expression [11][12][13][14][15]. The zebrafish model of ASD offers methodological advantages, including high socialization within the species, prolific reproductive performance, a broad behavioral repertoire, physiological and genetic homology, and neuroanatomical similarity to mammalian species, including humans [13].…”
Section: Introductionmentioning
confidence: 71%
“…For instance, DNA methylation changes in the oxytocin receptor gene have been linked to social deficits in individuals with ASD [ 12 ]. Similarly, alterations in gene expression involved in regulating the stress response have been linked to anxiety and depression in individuals with ASD [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using microarrays, whole-exome sequencing, and whole-genome sequencing have identified that rare de novo mutations as well as variations in single nucleotide polymorphisms are associated with ASD [ 3 , 4 , 5 ]. However, a consensus is emerging that the total fraction of ASD attributable to genetic inheritance may only be 40–60% [ 6 , 7 ]. Apart from a component of genetic heritability in the pathogenesis of ASD, epigenetic and environmental factors are also known to play an important role [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a consensus is emerging that the total fraction of ASD attributable to genetic inheritance may only be 40–60% [ 6 , 7 ]. Apart from a component of genetic heritability in the pathogenesis of ASD, epigenetic and environmental factors are also known to play an important role [ 7 , 8 ]. Environmental exposure to toxic chemicals has also been implicated in the etiology of ASD [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%